The development of Northern Sotho linguistic terminology for Higher Education in South Africa - Mmanape, Hlungwane (My University, 2020)
Terminology development is one of the key elements to the promotion of multilingualism and language development. Globally, the field of terminography has advanced through computer technologies, however, terminology development of indigenous African languages remains inadequate (Alberts, 2010). The aim of this study was to develop a Northern Sotho linguistics glossary for higher education. The study followed a qualitative method and thematic analysis approach. The English terms collected in this research were sourced from course material of the undergraduate syllabus in African languages at the University of the Witwatersrand and linguistics dictionaries. The Northern Sotho equivalents of the English terms were searched from Terminology and Orthography No.4, 1988(T&O, No.4), grammar books and Northern Sotho general dictionaries. The total amount of terms harvested in the source language were 163, from which, only 63 equivalents were found in Northern Sotho. The terms were purposively selected based on whether they appear in the undergraduate syllabus. The author followed the theory of onomasiology to study the nomenclature of Northern Sotho in order to coin neologisms. Terms found and coined were entered into a FLex program and produced the glossary. The significance of the study lies in the fact that it would increase the vocabulary of Northern Sotho by creating new special terms in the language. This will be essential in developing the language, but most importantly in facilitating learning in higher education for mother tongue speakers of the language
Research report submitted in partial completion of a Master’s Degree, Department of African Languages & Linguistics, in the Faculty of Humanities, University of the Witwatersrand, 2020